Trypanosoma cruzi Infects Human Dendritic Cells and Prevents Their Maturation: Inhibition of Cytokines, HLA-DR, And Costimulatory Molecules - Van Overtvelt, Laurence (American Society for Microbiology, 1999)
Trypanosoma cruzi, a parasitic protozoan, is the etiological agent of Chagas’ disease. Despite the many immune system disorders recognized in this infection and the crucial role played by dendritic cells (DC) in acquired immune responses, it was not known whether these cells could be infected by T. cruzi trypomastigotes and the consequences of such an infection on their immune functions. We now provide evidence that human monocyte-derived DC can be infected by T. cruzi and can support its intracellular multiplication. Interestingly, this infection has functional consequences on immature DC and on their maturation induced by lipopolysaccharide (LPS). First, after T. cruzi infection, the basal synthesis of interleukin-12 (IL-12) and tumor necrosis factor alpha (TNF-α) was impaired. Furthermore, the process of maturation of DC induced by LPS was drastically affected by T. cruzi infection. Indeed, secretion of cytokines such as IL-12, TNF-α, and IL-6, which are released normally at high levels by LPS-activated DC, as well as the up-regulation of HLA-DR and CD40 molecules, was significantly reduced after this infection. The same effects could be induced by T. cruzi-conditioned medium, indicating that at least these inhibitory effects were mediated by soluble factors released by T. cruzi. Taken together, these results provide new insights into a novel efficient mechanism, directly involving the alteration of DC function, which might be used by T. cruzi to escape the host immune responses in Chagas’ disease and thus might favor persistent infection.